Removal of methylene blue (MB) dye from water environment by processed Jowar Stalk [Sorghum bicolor (L.) Moench] adsorbent - Dod, Ramesh; Banerjee, Goutam; Saini, D. R. (Clean Technologies and Environmental Policy, 2015)
The present paper discusses the results of the study of adsorption of methylene blue on activated carbon, derived from cheap and abundantly available agro-residue of Jowar Stalk (JS) [Sorghum bicolor (L.) Moench] on suitable heat and acid treatment. The physico-chemical and morphological characteristics of processed carbon of JS origin were studied using X-ray diffraction, scanning electron microscopy, Brunauer, Emmett and Teller surface area, and Fourier transform infrared spectrophotometry analyses. The batch studies revealed optimum values of adsorption parameters such as pH, adsorbent dosage, agitation speed, grain size, temperature, and contact time as 7, 1.5 g l(-1), 200 rpm, finer than 75 A mu m, 30 A degrees C, and 7 h, respectively. The adsorption isotherm data were best described by Langmuir isotherm model with a maximum adsorption capacity of 176.05 mg MB g(-1) JS activated carbon at 30 A degrees C, which is higher than that available with adsorbents used by past researchers. In terms of cost-effectiveness, JS carbon shows its superiority over commercially available carbon.
Keywords: Adsorption; Isotherms; kinetics; Methylene blue; Processed Jowar Stalk [Sorghum bicolor (L.) Moench]